Analysis of ELP4, SRPX2, and interacting genes in typical and atypical rolandic epilepsy. Issue 8 (3rd July 2014) - Reinthaler, Eva M.; Lal, Dennis; Jurkowski, Wiktor; Feucht, Martha; Steinböck, Hannelore; Gruber‐Sedlmayr, Ursula; Ronen, Gabriel M.; Geldner, Julia; Haberlandt, Edda; Neophytou, Birgit; Hahn, Andreas; Altmüller, Janine; et al.
Summary Rolandic epilepsy (RE) and its atypical variants (atypical rolandic epilepsy, ARE) along the spectrum of epilepsy–aphasia disorders are characterized by a strong but largely unknown genetic basis. Two genes with a putative (ELP4) or a proven (SRPX2) function in neuronal migration were postulated to confer susceptibility to parts of the disease spectrum: the ELP4 gene to centrotemporal spikes and SRPX2 to ARE. To reexamine these findings, we investigated a cohort of 280 patients of European ancestry with RE/ARE for the etiological contribution of these genes and their close interaction partners. We performed next‐generation sequencing and single‐nucleotide polymorphism (SNP)–array based genotyping to screen for sequence and structural variants. In comparison to European controls we could not detect an enrichment of rare deleterious variants of ELP4, SRPX2, or their interaction partners in affected individuals. The previously described functional p.N327S variant in the X chromosomal SRPX2 gene was detected in two affected individuals (0.81%) and also in controls (0.26%), with some preponderance of male patients. We did not detect an association of SNPs in the ELP4 gene with centrotemporal spikes as previously reported. In conclusion our data do not support a major role of ELP4 and SRPX2 in the etiology of RE/ARE. A PowerPoint slide summarizing this article is available for download in the Supporting Information section here.